Single Entity Behavior of CdSe Quantum Dot Aggregates During Photoelectrochemical Detection - Subedi, Pradeep; Parajuli, Suman; Alpuche-Aviles, Mario A. (Frontiers in Chemistry, 2021)
We demonstrate that colloidal quantum (QDs) dots of CdSe and CdSe/ZnS are detected during the photooxidation of MeOH, under broad-spectrum illumination (250 mW/cm2). The stepwise photocurrent vs. time response corresponds to single entities adsorbing to the Pt electrode surface irreversibly. The adsorption/desorption of the QDs and the nature of the single entities is discussed. In suspensions, the QDs behave differently depending on the solvent used suspension the materials. For MeOH, CdSe is not as stable as CdSe/ZnS under constant illumination. The photocurrent expected for single QDs is discussed. The value of the observed photocurrents, > 1 pA is due to the formation of agglomerates consistent with the collision frequency and suspension stability. The observed frequency of collisions for the stepwise photocurrents is smaller than the diffusion-limited cases expected for single QDs colliding with the electrode surface. Dynamic light scattering and scanning electron microscopy studies support the detection of aggregates. The results indicate that the ZnS layer on the CdSe/ZnS material facilitates the detection of single entities by increasing the stability of the nanomaterial. The rate of hole transfer from the QD aggregates to MeOH outcompetes the dissolution of the CdSe core under certain conditions of electron injection to the Pt electrode and in colloidal suspensions of CdSe/ZnS